The catching efficiency of cod gillnets with different hanging ratio (E) and different floatline buoyancy. - Angelsen, Karl Kr.; Haugen, Kjeld; Floen, Svein (ICES, 1979)
The floatline buoyancy seems to influence the catching efficiency of cod gillnets. Trials with different byoyancies in cod gillnet fishing in Northern Norway gave the best catches with a buoyancy of about 65 grammes per metre floatline. Comparative fishing with nets of different hanging ratios showed that the usual hanging ratio in Norwegian cod gillnets E = 0.5, is not the most efficient one. The best catch per gillnet was obtained with a hanging ratio of about 0.6